The dyophysite christology of Cyril of Alexandria - Loon, Hans van, 1951- (Vigiliae Christianae, Supplements, 2009)
The formula 'one incarnate nature of the Word of God' has often been depicted as a summary of Cyril of Alexandria's (ca 378-444) christology. But no systematic study into his christological works has been published. Besides, there is no consensus regarding the meaning of the key terms and expressions in these works. This book addresses this deficiency by an integral investigation of the archbishop's christological writings during the first two years of the Nestorian controversy, and comes to the conclusion that his christology is basically dyophysite. This re-appraisal of his christology bears on the understanding of the Council of Chalcedon and on contemporary ecumenical relations, especially those between the Eastern Orthodox and the Oriental Orthodox.